PENDIDIKAN KESEHATAN TENTANG KEBUTUHAN NUTRISI UNTUK MENUNJANG AKTIVITAS ANAK USIA SEKOLAH - Martha, Anastasia Putu; Djoar, Raditya Kurniawan; Ekawati, Nora (Abdi Panca Marga, 2023)
Good nutritional status that can be used to support the physical activity of school-age children. The condition of partners obtained from the preliminary survey shows that school-age children do not have good knowledge of nutritional needs to support activities, including how to choose food ingredients and how to store food. Seeing health problems in community groups, prevention efforts must be prioritized through health education. With community groups understanding the importance of making efforts to improve nutritional needs to support activities, it is hoped that they can make a positive contribution to community groups to stay healthy, active, productive, useful and beneficial for themselves and the environment. This dedication partner is SDN Lidah Kulon I Surabaya. This community service is carried out by providing health education and mentoring to students. The results obtained are that the level of student knowledge increases after health education and assistance is carried out.